Analysis of the Influence of Online Comments, Logistics Service Quality, Promotion Incentive Information, and Promotion Time Limit on Impulsive Buying Behavior through Perceive Trust and Perceive Value in Shopee Application Users in Surabaya - Yuliana; Hananiel Mennoverdi Gunawan (Universitas Pelita Harapan, 2024)
The development of trade in Indonesia has the attraction of how a person buys goods through online media is increasing rapidly. By researching Shopee with customers in Surabaya, the aim is to determine the influence of Online comments (OC), Logistic Service Quality (SQ), Promotion Incentive Information (PI), Promotion Time Limit (PL) on Perceive Trust (PT) and Perceive Value (PV). This study also examines the influence of Perceive Trust (PV) and Perceive Value (PV) respectively on Impulsive Buying Behaviour (BB). The results of the regression test showed that Online comment (OC), Logistic Service Quality (SQ), Promotion Incentive Information (PI), Promotion Time Limit (PL) had a significant effect on Perceive Trust (PT). Online comment (OC), Logistic Service Quality (SQ), Promotion Incentive Information (PI), Promotion Time Limit (PL) have a significant effect on Perceive Value (PV). Perceive Trust (PV) and Perceive Value (PV) each have a significant effect on Impulsive Buying Behaviour (BB).